The Effect Of Incentives On Employee Performance In The Public Works And Spatial Planning Office Asahan Regency - Ira Junianty; Muhammad Isa Indrawan (Yayasan Multidimensi Kreatif, 2024)
This type of research is a causal associative quantitative research with the aim of analyzing the pattern of relationships between two variables and determining the influence of Incentives on Employee Performance. This research was carried out at the Office of Public Works and Spatial Planning of Asahan Regency, with a population of 145 employees. The sampling technique used is simple random sampling, where samples are randomly selected from the existing population. The data used came from the results of a questionnaire distributed to respondents consisting of all employees in various divisions. The results of the study show that Incentives have a positive and significant effect on Employee Performance. This is evidenced by a t-count value of 10.159, which is greater than the t-table 1.65543, and a significance value of 0.000, which is smaller than 0.05. A regression coefficient of 0.905 indicates that every 1 point increase in Incentives will lead to an increase in Employee Performance by 0.905 points, assuming other variables remain constant. In addition, the results of the determination coefficient test showed an Adjusted R Square value of 0.467 or 46.70%, which means that Incentives have a very high influence on Employee Performance, with the remaining 53.30% influenced by other factors that have not been studied in this study. Overall, the results of this study identify that increasing incentives can contribute to improving Employee Performance at the Asahan Regency Public Works and Spatial Planning Office.